UNPALPABLE UNDESCENDANT TESTES MANAGEMENT EVALUATION IN CIPTO MANGUNKUSUMO HOSPITAL - Siregar, Ginanda Putra; Rodjani, Arry; Wahyudi, Irfan (Indonesian Urological Association, 2015)
Objective: This study is to evaluate imaging modalities used in unpalpable undescended testes (UDT) patient at our centre. We evaluate the data descriptively. Material & methods: This is a descriptive and retrospective study. Data was taken from medical record in Cipto Mangunkusumo Hospital from January 2010 until June 2014. Sampling method is total sampling. Inclusion criteria for this study was unpalpable UDT patients at Urology Department Cipto Mangunkusumo Hospital, whereas patients with incomplete data and have XX chromosomes were excluded. Results: Mean ages in this study was 9.35 years old (7 month to 41 year old). Diagnostic tools was not performed in half of the patients. Abdominal ultrasound was performed in 9 patients (34.6%), and 4 patients with CT-Scan. We found that most of patients were unilateral UDT (57.7%). Bilateral UDT was found in 11 patients (42.3%). Twenty one patients undergo laparoscopic orchidopexy (80.8%). There were 7 patients undergo full laparoscopy orchidopexy. Fowler Stephen technique applied to 4 patients, and eleven patients underwent inguinal exploration and orchidopexy. Laparoscopic biopsy was performed in 4 patients and agenesis of the testis was found in one patient. There are 13 cases with other abnormalities; hypospadias (38.5%), DSD 46 XY (53.8%), and testicular tumor (7.7%). Conclusion: Unpalpable UDT is adequately diagnosed by history and physical examination. Half of our patient in this study were not performed additional examination such as ultrasound, CT-Scan, and MRI for diagnostic tools and directly underwent laparoscopic orchidopexy. The best management of unpalpable UDT is laparoscopic orchidopexy.